2022
DOI: 10.3389/fnut.2022.972100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical distancing by COVID-19 pandemic on diet quality, neurological and immunological markers, and fecal microbiota of Brazilian older women

Abstract: Physical distancing was used to prevent transmission of COVID-19, however there are concerns that this may promote harmful impacts on health, such as reduced levels of physical practice and changes in food intake and gut microbiota composition. This study evaluated the impacts of 6 months physical distancing on Brazilian older women upon body mass index (BMI), strength, physical activity level (IPAQ), eating habits, neurological markers (brain-derived neurotrophic factor-BDNF and cortisol), cytokines (IL-2, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 124 publications
0
1
0
Order By: Relevance
“…On the other hand, light-to-moderate exercise has been shown to be superior to intense exercise in improving health and longevity. A study on Brazilian women aged over 60 showed a strong positive correlation between light physical activity and klotho levels [5]. Overall, this is consistent with the literature, which states that moderate physical activity improves life expectancy and longevity compared to a sedentary lifestyle [66].…”
Section: Physical Activitysupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, light-to-moderate exercise has been shown to be superior to intense exercise in improving health and longevity. A study on Brazilian women aged over 60 showed a strong positive correlation between light physical activity and klotho levels [5]. Overall, this is consistent with the literature, which states that moderate physical activity improves life expectancy and longevity compared to a sedentary lifestyle [66].…”
Section: Physical Activitysupporting
confidence: 86%
“…One way to prevent and even reverse chronic diseases is through lifestyle changes through health promotion and education [4]. This also helps delay the onset of geriatric syndrome (frailty, cognitive decline, and reduced performance in the activities on the daily living scale) [5]. This is why a new discipline of medicine has emerged to specifically address this issue: lifestyle medicine [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there have been some reports on the association between Blautia and exercise habits. In a study focusing on women, a positive correlation between Blautia and exercise intensity was reported [ 37 ]. Moreover, a report on childhood obesity, including both men and females, suggested that a 12-week exercise program combining strength training and aerobic exercise might lead to an increase in Blautia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%